2019
DOI: 10.3389/fmicb.2019.02849
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Modulates Cell Surface Hydrophobicity in Acinetobacter baumannii

Abstract: Acinetobacter baumannii, a Gram-negative coccobacillus, has become a prevalent nosocomial health threat affecting the majority of hospitals both in the U.S. and around the globe. Microbial cell surface hydrophobicity (CSH) has previously been correlated with virulence, uptake by immune cells, and attachment to epithelial cells. A mutant strain of A. baumannii (ΔtrxA) lacking the redox protein thioredoxin A was found to be more hydrophobic than its wild type (WT) and complemented counterparts, as measured by bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Thus, MATH assay was done to assess the effect of EPS reduction on CSH of control and myrtenol treated cells. The result of MATH assay showed significant inhibition in the CSH of myrtenol treated sample which can be corroborated with the above theory and as well as another report 27 . The presence of flagella, pili and fimbriae in AB promotes the bacterial motility and biofilm formation.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, MATH assay was done to assess the effect of EPS reduction on CSH of control and myrtenol treated cells. The result of MATH assay showed significant inhibition in the CSH of myrtenol treated sample which can be corroborated with the above theory and as well as another report 27 . The presence of flagella, pili and fimbriae in AB promotes the bacterial motility and biofilm formation.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the pathogen successfully invaded mouse MH-S, TC-1, MLE-12, and Drosophila S2 cells (Figure 1A). However, the levels of bacterial invasion was significantly lower in these cells compared to J774 cells, a murine macrophage-like line that has been previously shown to be susceptible to invasion by A. baumannii (Asplund et al, 2013;May et al, 2019). To confirm our findings, we used gentamicin protection assays to analyze intracellular persistence or replication of the pathogen during a time course of infection.…”
Section: A Baumannii Infection Induces Host Cell Death In Alveolar Macrophages But Not Lung Epithelial Cellssupporting
confidence: 59%
“…14,35 Furthermore, TrxA-mediated modulation of bacterial surface hydrophobicity via disulfide bond reduction and regulation of type IV pili is a contributing factor to A. baumannii virulence. 36 The mechanism(s) for TrxAmediated differential OMV protein packaging remains to be determined; however, the TrxA-mediated alteration of cell hydrophobicity may play a role.…”
Section: Discussionmentioning
confidence: 99%